Entrepreneurs and their Impact on Knowledge Diffusion, Jobs and Economic Growth in Kurdistan Region Government - Ghafur Hamadamin, Hawar; Mahdi Azeez, Tavga; Hawbashfaisalsuliman, (International Journal of Psychosocial Rehabilitation, 2019)
The big importance of the relationship between the effect of entrepreneurship on knowledge diffusion, jobs, and economic growth is not new because any correct decision in the modern economic situation will come from the correct decision by the entrepreneurship to start a new small business and increase the capital for it. The importance of this study is to determine the entrepreneur and the impact of critical issues inside the environment of the economy in the country, such as understanding and evaluating the knowledge diffusion and finding the remedies of the job opportunities section, and finally increasing and motivating the economic growth by integrating procedures with other important sections, such as finding the reasonable way of achieving the economic sections.